Superior Service Management Strategy for Administrative Staff in High Schools - Kusuma, Aditya Andre; Prasojo, Lantip Diat (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
School administrative staff (TAS) is the suboptimal implementation of excellent service, which is caused by limited technology, lack of training, and heavy workload. This has an impact on the quality of administrative services that are not in accordance with standard operating procedures (SOP), thus reducing the satisfaction of various related parties in the school environment. This study aims to analyze the formulation of superior service management strategies for administrative staff in high schools. The subjects of the study were six high school administrative staff. The study used a descriptive qualitative method with data obtained through observation, interviews, and documentation. The data analysis used was data collection, data reduction, data presentation and verification. The results of the analysis showed that the formulation of excellent service management was carried out by strengthening the competence and innovation of the quality of administrative staff, thus supporting the creation of quality services in high schools. Its implementation is realized through attitudes, attention, and actions that accommodate aspirations, dynamics of science, and technology in order to create superior and quality high schools. The conclusion of the study shows that the strategy for excellent service management in high schools involves formulations that involve all related parties, including principals, teachers, employees, and administrative staff.